2014
DOI: 10.1089/gtmb.2014.0066
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Monoamine Oxidase Gene Polymorphisms and Attention Deficit Hyperactivity Disorder in Korean Children

Abstract: Attention deficit hyperactivity disorder (ADHD) is a common disorder of the school-age population. ADHD is familial and genetic studies estimate heritability at 80-90%. The aim of the present study was to investigate the association between the genetic type and alleles for the monoamine oxidase (MAO) gene in Korean children with ADHD. The sample consisted of 180 ADHD children and 159 control children. We diagnosed ADHD according to DSM-IV. ADHD symptoms were evaluated with Conners' Parent Rating Scales and Dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We analyzed a total of 472 samples from the Children’s Health and Environmental Research (CHEER) cohort study and a previous study described in [ 32 ]. Of these samples, 120 ADHD children, 322 control individuals were a subset of the CHEER cohort study and 30 ADHD children were a subset of the samples analyzed in Kwon et al (2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed a total of 472 samples from the Children’s Health and Environmental Research (CHEER) cohort study and a previous study described in [ 32 ]. Of these samples, 120 ADHD children, 322 control individuals were a subset of the CHEER cohort study and 30 ADHD children were a subset of the samples analyzed in Kwon et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…The Bonferroni correction was applied to adjust the α-level according to the number of markers (<0.05/2 = 0.025). It has been reported that approximately 210 subjects are needed to obtain a 95% sample power in a case-control study of ADHD in the Korean population [ 32 ]. In this study, we expected that there was sufficient power to evaluate the effects between the MAOA gene polymorphisms and ADHD.…”
Section: Methodsmentioning
confidence: 99%
“…Rs6323, a number of other SNPs, and uVNTR have been associated with ADHD in haplotype analyses, with the MAOA-L alleles and rs6323 G-allele contributing to the risk (Domschke et al, 2005;Hwang et al, 2018;Xu et al, 2007;Faraone and Mick, 2010;Kwon et al, 2014;Rommelse et al, 2008). For example, in an Indian population, the risk alleles of several SNPs in the MAOA gene, including the G allele of the rs6323 polymorphism, and uVNTR MAOA-L allele in haplotype with rs6323, were preferentially transmitted from mothers to ADHD probands, this was detected only in male probands, and was suggested by the author as one of the possible reasons for higher ADHD prevalence in males.…”
Section: Maoamentioning
confidence: 99%